Evaluasi Kompetensi Mengajar Mahasiswa setelah Melaksanakan Praktek Lapangan Kependidikan pada Jurusan Kelistrikan di Kota Padang - Ta'ali Ta'ali; Nadatul Nazhifah Deona (Jurnal Pendidikan Teknik Elektro, 2023)
This study aims to describe the evaluation of students' competence in implementing PLK in electrical engineering majors to support the achievement of PLK goals and describe the differences in teaching competence of these students with other students who carry out PLK in different places but in the same city, namely Padang City. Education students at UNP are prepared to become competent and professional teacher candidates so that students are equipped from the start with the implementation of an educational field practice program by mastering various materials regarding education as a whole. Therefore the implementation of the PLK program needs to be evaluated for better program development. This research uses a quantitative approach with the type of evaluation research using the Goal Oriented Evaluation Model. The object of this research is the teaching competence of students. The subjects of this study were UNP Electrical Engineering Education students class of 2019 who had completed PLK. This research instrument uses a questionnaire. Based on the questionnaire data analysis results in terms of the four aspects of the assessment. From the results of the calculation of the frequency distribution of the 4 aspects of competency assessment, it can be seen that the pedagogical, personality and social competencies of students are in the very good category, while the professional competence is in the good category. In addition, there is no significant difference between the teaching competencies of students who carry out PLK majoring in electricity in the city of Padang.